Human enterovirus infection in stray dogs. Some aspects of interest to public health Infecção por enterovirus humanos em cães errantes. Alguns aspectos de interesse em Saúde Pública - Eliseu Alves Waldman; Regina C. Moreira; Sueli G. Saez; Denise F.C. Souza; Rita de C.C. Carmona; Sueko Takimoto; Valdson de A. Cortes (Revista do Instituto de Medicina Tropical de São Paulo, 1996)
To investigate the possible role of domestic animals as reservoirs of human enteroviruses, we studied 212 stray dogs captured in different areas of the municipality of São Paulo. The captured animals were divided into 19 groups of 10 to 20 dogs each; faeces of 126 of the 212 dogs were processed for enterovirus isolation. The following viruses were isolated from 12 dogs: poliovirus type 1 (2 dogs), poliovirus type 3 (1 dog), echovirus type 7 (8 dogs) and echovirus type 15 (1 dog). Of the 12 infected animals, four had specific homotypic neutralizing antibody titres > 16. All 212 animals were tested for the presence of neutralizing antibodies to human enteroviruses. The frequency of neutralizing antibodies present in titres of > 16 was 10.3%, 3,8% and 4.3% for vaccinal prototypes of polioviruses 1, 2 and 3 respectively; 1,9%, 1.4% and 1.5% for wild prototypes of the same viruses, 11.3% for echovirus 7, and 2.4% for echovirus 15. The proportion of dogs with neutralizing antibodies varied with the virus studied. Some indication of the susceptibility of dogs to infection with human enteroviruses was demonstrated, and the importance of this fact for the Plan for Global Eradication of the Wild Poliovirus is discussed. Foram estudados 212 cães errantes, capturados em áreas periféricas do município de São Paulo, com o objetivo de investigar o possível papel desses animais como reservatórios de enterovírus humanos. Os animais capturados foram divididos em 19 grupos compostos por 10 a 20 animais cada um. Foram efetuadas tentativas de isolamento em amostras de fezes em 126/212 cães, obtendo-se resultados positivos em 12 deles, assim distribuídos: poliovirus tipo 1 (dois cães), poliovírus tipo 3 (um cão), echovirus tipo 7 (oito cães) e echovirus tipo 15 (um cão). Dos 12 animais infectados, quatro apresentaram anticorpos neutralizantes homotípicos com títulos > 16. Todos os 212 cães foram submetidos a pesquisa de anticorpos neutralizantes contra enterovírus humanos. As frequências de anticorpos neutralizantes com ...